Molecular mechanisms involved in inflammasome activation - Bryant, Clare; Fitzgerald, Katherine A. (Trends in cell biology, 2009)
Germline-encoded pattern recognition receptors (PRRs) sense microbial or endogenous products released from damaged or dying cells and trigger innate immunity. In most cases, sensing of these signals is coupled to signal transduction pathways that lead to transcription of immune response genes that combat infection or lead to cell death. Members of the NOD-like receptor (NLR) family assemble into large multiprotein complexes, termed inflammasomes. Inflammasomes do not regulate transcription of immune response genes, but activate caspase-1, a proteolytic enzyme that cleaves and activates the secreted cytokines interleukin-1β and interleukin-18. Inflammasomes also regulate pyroptosis, a caspase-1-dependent form of cell death that is highly inflammatory. Here, we review exciting recent developments on the role of inflammasome complexes in host defense and the discovery of a new DNA sensing inflammasome, and describe important progress made in our understanding of how inflammasomes are activated. Additionally, we highlight how dysregulation of inflammasomes contributes to human disease.